A narrative review of factors associated with the development and progression of non‐alcoholic fatty liver disease. Issue 4 (2nd August 2019) - De Nooijer, Annemiek; Vreugdenhil, Anita; Karnebeek, Kylie; van Hasselt, Peter M.; Fuchs, Sabine A.
Summary: Background: With the obesity pandemic, non‐alcoholic fatty liver disease (NAFLD) has become the most prevalent liver disease. NAFLD can progress to non‐alcoholic steatohepatitis (NASH), a potential cause of liver failure. It remains difficult to identify patients at risk for NASH, despite evolving insights in contributing factors, including genetic variance, hormones, adipokines, diet and body‐fat distribution. We aimed to present a broad perspective on these risk factors associated with NAFLD development and progression with a focus on their contribution in different age groups and susceptible high‐risk populations, hereby giving insight in the pathophysiology of NAFLD. Methods: Literature was searched for relevant articles on the pathophysiology of NAFLD in different age groups. Results: Our review underscores large contributions of diet, with particularly fructose promoting NASH development, and sex hormones, with oestrogens exerting protective effects and androgens negatively influencing NAFLD development. Genetic variation in corresponding pathways might further determine NAFLD progression. Conclusions: Changes throughout the transition from childhood to adulthood show that variations in diet, hormone levels and metabolism are related to NAFLD progression. The human body uses different strategies to handle excessive nutrients, but each comes at a price. When corresponding pathways are strained by hormonal or genetic factors, NASH or other symptoms of the metabolic syndrome ensue. Potentially, stratification based on sex, body‐fat distribution, diet, lifestyle, microbiome, adipokines, sex hormones, blood concentrations of liver enzymes, liver histology and genetic pre‐disposition might help to identify patients at increased risk of NASH.